2016
DOI: 10.1158/0008-5472.can-15-2220
|View full text |Cite
|
Sign up to set email alerts
|

M-COPA, a Golgi Disruptor, Inhibits Cell Surface Expression of MET Protein and Exhibits Antitumor Activity against MET-Addicted Gastric Cancers

Abstract: The Golgi apparatus is responsible for transporting, processing, and sorting numerous proteins in the cell, including cell surfaceexpressed receptor tyrosine kinases (RTK). The small-molecule compound M-COPA [2-methylcoprophilinamide (AMF-26)] disrupts the Golgi apparatus by inhibiting the activation of Arf1, resulting in suppression of tumor growth. Here, we report an evaluation of M-COPA activity against RTK-addicted cancers, focusing specifically on human gastric cancer (GC) cells with or without MET amplif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 45 publications
(50 reference statements)
1
25
0
Order By: Relevance
“…Recent studies showed that M-COPA has an anti-cancer effect in Met tyrosine kinase-addicted cancers in vivo through inhibition of the trafficking of the receptor to the PM [3133]. Therefore, we investigated the effect of M-COPA on oncogenic Kit signalling in neoplastic mast cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies showed that M-COPA has an anti-cancer effect in Met tyrosine kinase-addicted cancers in vivo through inhibition of the trafficking of the receptor to the PM [3133]. Therefore, we investigated the effect of M-COPA on oncogenic Kit signalling in neoplastic mast cells.…”
Section: Resultsmentioning
confidence: 99%
“…However, BFA has less stability in vivo while the others exhibit weaker inhibition of cell growth, and their development as drugs has not progressed. On the other hand, M-COPA had an anti-cancer effect in vivo experiments using breast cancer or gastric cancer xenograft models [32,33], and it is now considered a novel anticancer drug candidate. Together with the fact that M-COPA suppressed imatinib-resistant Kit signalling, inhibition of receptor trafficking is a promising approach for the treatment of cancers bearing a resistant mutation to targeting therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other strategies to impair the ER-Golgi network are being currently pursued as anti-cancer therapy. For example, the M-COPA (2-methylcoprophilinamide) compound, inhibiting Arf1 (ADP ribosylation factor 1) involved in COPI and clathrin-coated transport vesicles, has been shown to disrupt the Golgi apparatus and RTK translocation to the membrane, to have antitumor effects against MET-addicted gastric cancers, and to overcome TKI resistance in EGFR-mutated non-small-cell lung carcinoma [124,125].…”
Section: Validation Of Noa Targetsmentioning
confidence: 99%
“…1A) (Ohashi et al 2012). Very recently, it has been reported that M-COPA exerts antitumor activity by inhibiting cell surface expression of MET protein in MET-addicted gastric cancers (Ohashi et al 2016). In this study, we explored the action of M-COPA as a novel suppressor of apoptosis in Stx-treated cells.…”
Section: Introductionmentioning
confidence: 99%